The Effect of Alternating Heading Exercises on Heading Skills at the Football Club - Hartanto, Hari; Wardiah, Dessy; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to find out: 1) the effect of Heading training on the ability of Heading in a football club at SMA Negeri 3 Tebing Tinggi Kabupaten Empat Lawang? 2) The Effect of Alternating Heading Exercises on Heading Ability at Football Clubs at SMA Negeri 3 Tebing Tinggi Kabupaten Empat Lawang? The research method used is experimental Eresearch. The population in this study was all Football Clubs at SMA Negeri 3 Tebing Tinggi Empat Lawang Regency with a total of 20 people, while the sampling technique used total sampling or census research with a total of 20 people divided by original pairing. The data collection technique uses a single heading test (Juggling Heading) football game for 30 seconds using forehead and measurement and using t test statistics. Based on the results of the study, it can be concluded that there is an influence of alternating Heading exercises on the ability of Heading in the Football Club at SMA Negeri 3 Tebing Tinggi Empat Lawang Regency. Taken together, the results showed that there was an effect of alternating heading exercises on the ability of heading in the Football Club at SMA Negeri 3 Tebing Tinggi Kabupaten Empat Lawang.